Financial Literacy and Financial Inclusion as Tools to Enhance Small Scale Businesses’ Performance in Southwest, Nigeria - Sajuyigbe, Dr. Ademola Samuel; Odetayo, Tajudeen A.; Adeyemi, Adewumi Z. (Finance & Economics Review, 2020)
Purpose: The study sought to examine the impact of financial literacy and financial inclusion on small businesses’ overall performance with special reference to Southwest Nigeria. Methods: Descriptive survey research sketch was adopted for this study, while the purposive sampling method was employed to choose forty small scale businesses registered with SMEDAN from each state capital of South Western of Nigeria that engaged in petty trading, bakeries, block-making, soup-making, tailoring, and agro-allied, totaling 240 participants as a sample size for the study. Data were collected by using a closed-ended questionnaire designed for the study, while simple percentage, mean, standard deviation, Pearson Product Moment Correlation (PPMC), and Ordinary Least Square (OLS) was used to analyze the data. Results: The findings disclose that financial literacy and financial inclusion jointly and independently affect small businesses’ performance. It revealed a positive and significant relationship between financial literacy and financial inclusion. However, the study depicts that majority of business operators did not have financial knowledge such as working capital management, accounting records system, financial reporting, cashbook maintenance, income statement, daily cash reconciliation, internal control on cash, and cash budget. Also, the study confirmed that the majority of small business entrepreneurs are financially excluded from micro-financing, emergency loans, employ purchase financing, business bank loans, and micro-insurance plan Services. Implications: The implication of this study is that if the Central Bank of Nigeria partnership with other professional organizations to promote financial literacy and inclusion programs to all business entrepreneurs across the nation, it will motivate more business entrepreneurs in Nigeria to have access to finance.